Issues of residential property division in Latvia: impact of Residential Property Law amendments on residential project development in several phases - Sevišķis, Allans (Riga Graduate School of Law, 2018)
The Amendments to the Law on Residential Property, effective from 13 July 2017, have revised the Law on Residential Property, which has been in force since 1 January 2011. The new regulation was aimed to determine clear management and maintenance payment system and clarify the joint property share calculation procedure when dividing a residential building in residential properties. The aim of the Master Thesis is to identify obstacles to new residential project division in residential properties and the impact on commercial practice caused by the Amendments to the Law On Residential Properties. In thesis it was concluded, that the changes in the Law have created an additional burden on development of new projects, increased direct costs associated with land division, and caused losses due to project delays. Consequently the Amendments to the Law On Residential Properties impose encumbrances to new multi-apartment project implementation and have a negative impact on new residential property development.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Private law::Property and real estate law; Latvia; Residential property